Chinese herbal prescriptions for COVID-19 management: Special reference to Taiwan Chingguan Yihau (NRICM101) - Su, Yi-Chang; Huang, Guan-Jhong; Lin, Jaung-Geng (Frontiers in Pharmacology, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), termed COVID-19, is a highly contagious disease. As at February 2022, increasing numbers of newly diagnosed COVID-19-associated pneumonia cases worldwide have attracted close attention from the international community. Currently, no small-molecule antiviral agents exist that can treat COVID-19-associated pneumonia and its associated high mortality rate. Traditional Chinese medicine (TCM) plus Western medicine (i.e., integrative medicine) has played an important role in Taiwan's fight against COVID-19. This review and critical analysis of the literature highlights the potential of TCM to prevent and treat COVID-19 via antiviral, anti-inflammatory and immunomodulatory activities, with evidence showing that many TCM components acting upon multiple targets and pathways. TCM substances with the potential to fight against COVID-19 include licorice, fish needle grass, Houttuynia cordata, Isatidis, tangerine peel, skullcap, and salvia, amongst others. Famous TCM formulas include Qing-Fei-Pai-Du-Tang (QFPDT), Lianhuaqingwen Capsule (LHC), Taiwan Chingguan Yihau (NRICM101), and Jing Si herbal drink (JSHD). In particular, the botanical preparation NRICM101, developed in 2020 for use in viral respiratory tract infections, effectively reduces proinflammatory cytokines and promotes antiviral, anti-inflammatory and immune responses. NRICM101 has been adopted for use in Taiwan for the clinical treatment of COVID-19. This review aims to provide reliable evidence demonstrating the therapeutic efficacy of TCM substances in support of their further development against novel coronavirus infectious diseases in Taiwan.